Civil enforcement rules and mechanism in China: the past, present and the future. (2nd January 2021) - Cao, Zhixun
ABSTRACT: A well-functioning enforcement court is the most crucial safeguard for the success of enforcement, which attracts the attention both internationally and domestically. Civil procedure law statute and its related judicial interpretations, which are experiencing rapid changes and still to be improved, consist of valid rules in the area of enforcement law. After enforcement proceedings are implemented in fact, the difficulty in enforcement began to be taken as a key issue in practice and therefore, led to reform efforts both politically and legally. The ordinary operation of enforcement proceedings could be divided into three parts: commencement and termination of the proceedings and the main part of the procedure. Besides the comparatively well-accepted enforcement rules, the special emphasis in China on the enforcement notice, the Internet-based control and sale of the debtor's assets and the special possibility of terminating proceedings while admitting failure in enforcement deserve more careful observation. As a general rule, the enforcement court is responsible for the discovery of debtor's assets, though the current reform plan intends to mitigate the investigative burden of the court. The Chinese judiciary has already announced some general framework in its reform plan. Despite we are undoubtedly concentrating on the developing solution of Chinese problems at national level, there is a strong need to take comparative experience more seriously. Only in this way could Chinese outstanding system of academic discourse be constructed firmly and eventually.